Research trends in the Deanate of Humanities and Art. Centrooccidental University “Lisandro Alvarado” (Revista Electrónica REDINE, 2023)
The purpose of this study is to present the research propensities adopted by the students of the Bachelor's Programs in Psychology, Art, Music and Human Development, belonging to the Dean of Humanities and Art (DEHA), at the Universidad Centroccidental “Lisandro Alvarado”, at the time of constructing and presenting his Special Degree Work (TEG). In this sense, a documentary investigation was carried out, based on the Data stored in the Central Library “Dra. María Gómez”, located on the aforementioned university campus. In addition to this bibliographic study, descriptive statistics (frequency and percentage) were applied to accurately specify the research approaches used in the various TEGs of each of these programs. It is worth noting that research trends at DEHA will depend on the degree that students are studying. That is to say, there is a preference towards the application of the quantitative approach (the numerical, the objective, the measurement) in the Psychology program and in the Human Development, Art and Music programs, their inclination is towards the qualitative aproche (the interpretation of language, gestures, symbols). Assertions that allow us to reflect and ask ourselves, Why is there not a balanced balance of research approaches (quantitative and qualitative) when constructing the academic products of graduates? Therefore, it is recommended to carry out similar studies that access other variables and research dimensions linked to this type of topic and thus archive a Deep understanding of the origin of these results. Likewise, it is substantial to seek to promote and explain the incidences of quantitative and qualitative research approaches, when approaching and studying the object of study or social phenomenon of interest to be investigated.
Keywords: research trends; research approaches; paradigms; types of research